Electronic Word of Mouth (e-WOM) and Purchase Intention: A Brief Look at the Last Decade by Bibliometrics - Kusumadewi, Afifah Nur'aghnia; Widowati, Retno (Dinasti International Journal of Economics, Finance & Accounting, 2026)
Electronic word of mouth (e-WOM) plays a crucial role in digital marketing by shaping consumer judgments and purchase decisions. This study conducts a bibliometric analysis of research on e-WOM and purchase intention published between 2015 and 2024. A total of 200 Scopus-indexed journal articles were analyzed using performance indicators, citation analysis, keyword co-occurrence, thematic clustering, and network visualization with VOSviewer. The findings reveal three development phases: emergence (2015–2017), rapid growth (2018–2020), and consolidation with a sharp increase in publications in 2023–2024. Influential journals and highly cited studies emphasize information helpfulness, review quality, and credibility as key predictors of purchase intention. Five thematic clusters were identified, covering consumer behavior, trust, social commerce, brand constructs, and information quality. The study confirms that e-WOM and purchase intention remain evolving research areas, highlights cross-cultural and longitudinal gaps, and provides structured directions for future theoretical and managerial development.